TO STUDY THE PRESENCE OF RISK FACTORS FOR THE DEVELOPMENT OF ACUTE CORONARY SYNDROME IN PATIENTS OF WORKING AGE HOSPITALIZED IN EMERGENCY MEDICAL CARE - Khasanjanova F.O; Fayzullayeva D.U (Scholar Express Journals, 2024)
To study the presence of risk factors for the development of acute coronary syndrome in young patients in specialized cardiology centers
Keywords: syndrome; factors; coronary; young